Impact assessment of investments in education on the development of human capital and its influence on the economic growth - Bulasheva, A.A.; Kusayinov, T.A. (BUKETOV BUSINESS REVIEW, 2019)
The study of the social role of higher education and its «contribution» to economic growth led to the conclusion that it is generated by expanding the amount of used labor and capital resources, as well as by improving their quality based on advances in technology and education. As a result, nowadays considerable attention has been paid to the study of human capital as the primary lever of economic growth. It is shown that the main indicator determining the potential of industries development and the region as a whole is a gross regional product (GRP), which characterizes the potential of the regional economy. The choice of factors for assessing and building of forecast models of GRP leads to the activation of regional and national policies and to the decline of the level of interregional imbalances. The relevance of the study of methods of estimating GRP and methods for its prediction is determined. The interrelation of the level of GRP from a number of statistical indicators characterizing the development of the region development, particularly education was revealed. The novelty of the research is the construction of the correlation-regression dependence of GRP on education costs, assessment of the significance and closeness of the connection of factors, identification of the applicability of the model for predicting GRP. Statistically significant regression equation is obtained that adequately describes the effect of costs on the level of GRP. The forecasting of the level of the GRP will allow planning the volumes and distributing the appropriate financial flows in order to increase the level of regional socioeconomic development.